The strategies of happy married couples (The Journal of Psychology and Sociology, 2017)
This article discusses one of the most actual problems of social psychology and social work,the problem of modern family and the strategy of happy married couples, who are the basis of every family.There are a lot of happy married couples in the world. Their fate causes a natural interest of people, because everyone wants to create such a happy family, which is based on trust, sympathy, respect and understanding. In this regard, the article gives a comparative analysis of the couples from different countries. A peculiarity of this article is statistical material presented along with the strategies of happycouples. Particular attention is paid to the analysis of British scientists who studied the main problems of the family based on the large statistical data. People often ask: «Why do some couples’ relationship get stronger with time, while others’are getting cool?». British psychologist says that happy couples are trying to see only positive quality in each other, thank each other and their destiny for this meeting every day, enjoy each day of living together. Unhappy couples only notice the negative qualitiesand emphasize the shortcomings of each other, constantly accuse each other in their unsuccessful situations. John Gottman, watching the conversation between couples, could predict the future of the marital relationship by 100%. It would seem hard to believe in this forecast, but the 40-year-old experience of these observations and analyzes inspires to trust to researcher. They created the so-called «laboratory of love.» Activity of the laboratory is also given in the article. A special part ofthe article is devoted to the analysis of the family life of political leaders such as M.S.Gorbachev andN.A.Nazarbayev, and their wives Raisa Gorbachev and Sara Nazarbayeva. Was described the strategy of couples,which is a basis for building a happy family, the foundation of a reliable and strong family.
Keywords: happy married couples; happy family; love; respect; feelings; conflict; a lifelong friend; understanding; caring attitude towards each other; responsiveness; capacity for joy; spiritual attachment.